(untitled) (Bangladesh Journal of Agricultural Research, 2015)
Twenty five yellow inbred lines of normal maize were evaluated for eleven parameters to study the genetic divergence using Mahalonabiss D2 and Rao s canonical variate analysis. The twenty five inbreds fell into five distinct clusters. The intra-cluster distance in all the five clusters was more or less low, indicating the genotypes within the same clusters were closely related. The highest intercluster distance was observed between cluster I and VI and the lowest between the cluster II and III. The cluster IV and V each contained the highest number of genotypes. Cluster V showed the highest mean values for kernel yield and all the yield contributing traits except 1000-kernel weight and cluster II had the lowest mean values for plant and ear height and maturity characters. Days to silking, ear length, number of kernels/row, 1000-kernel weight and kernel yield showed maximum contribution towards total divergence among different characters. Based on medium to high inter-cluster distances, per se performances and desirable traits, fourteen yellow inbred lines viz. BIL 77, BIL 97, CML 287, CML 470, CML 480, CML 486, CZ 2370-22-2, CZ 2370-24-3, CZ 2370-28-2, CZ 23 70-31-3, IPB 911-2, IPB 911-22, IPB 911-36 and IPB 911-50 were selected for future hybridization program. Crossing between these genotypes have the chance to obtain higher heterosis with high performing crosses. DOI: http://dx.doi.org/10.3329/bjar.v39i4.22531 Bangladesh J. Agril. Res. 39(4): 553-561, December 2014